Impact of Advanced Glycation End products (AGEs) and its receptor (RAGE) on cancer metabolic signaling pathways and its progression - Muthyalaiah, Yadav Sangeeta; Jonnalagadda, Bhavana; John, Cordelia Mano; Arockiasamy, Sumathy (Glycoconjugate journal, 2021)
Cancer is a complex disease with a 5–10% hereditary base, but nutrition, lifestyle, and the environment we are exposed to influence 90–95% of cancers. Due to rapid westernization, the diet we consume is rich in advanced glycation end products (AGEs). AGEs are the heterogeneous group of compounds formed by non-enzymatic reactions between reducing sugars and amino groups of proteins, lipids, and nucleic acids. Its implication is confirmed in many chronic conditions such as diabetes, renal, cardiovascular diseases, and aging however its role in cancer development has been understudied. Cancer cells are continuously exposed to AGEs due to their increased production, owing to its high metabolic rate and aerobic glycolysis. AGEs accumulation led to glycative stress which in turn stimulates oxidative stress and inflammation, through its receptor known as receptor for advanced glycation end products (RAGE). RAGE mediates crosstalk between the tumour cells and its microenvironment components to induce hypoxia, mitochondrial dysfunction, endoplasmic reticulum stress, autophagy, epigenetic modification, and cancer stemness. This emphasizes AGEs as an essential driving factor in different aspects of cancer development, but the exact molecular mechanism has to be explored. Thus, this review gives an insight into the pathological role of AGEs at the bio-molecular level in the tumourigenesis and progression of cancer in terms of the tumour microenvironment, invasion, and metastasis. Further, the compiled clinical data relating to the AGE-RAGE axis associated with different cancers and its potential inhibitors have been discussed.